Pengembangan Alat Peraga Biologi Berbasis Instgarm Terintegrasi Nilai- Nilai Keislaman Pada Materi Sistem Peredaraan Darah Manusia Kelas XI - Allia Nur Aliffah; Achmad Ali Fikri; Setiati Hidayah (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research uses Research and Development (RnD) research, with a 4D development model. This research aims to find out how the product is developed and the level of feasibility through media, material and Islamic validation as well as the practicality of teachers and students. Data collection techniques for product development are through observation, interviews, questionnaires and documentation. Next, the data obtained was analyzed using quantitative descriptive analysis. This research produces a product in the form of an Instagram-based biology teaching aid integrated with Islamic values ​​in the human circulatory system material. This product meets the valid and practical criteria by obtaining a validity assessment of 88.84% in the "very valid" category, validation results by material expert lecturers, obtaining a validity assessment of 88.2% in the "very valid" category and validation results by expert lecturers Islamic, a validity assessment of 88.83% was obtained in the "very valid" category. Meanwhile, practicality was determined by the biology teacher and class XI MA students. Based on the practicality results by biology teachers, a practicality assessment of 88.05% was obtained in the "very practical" category and practicality results by class XI high school students, a practicality assessment of 84.4% was obtained in the "very practical" category. Thus, Instagram-based biology teaching aids integrated with Islamic values ​​are suitable for use as interactive learning media to test effectiveness at the next stage.